How Does the Performance of Islamic Microfinance Institutions Affect the Welfare of SMEs?: Empirical study of BTM Mulia Babat - Hakimi, Fifi; Maf'ula, Faricha; Syahidin, M. Ramizal (Universitas Muhammadiyah Surakarta, 2024)
This study aims to assess the direct and indirect effectiveness of Islamic microfinance services, particularly financing products, in enhancing the welfare of small and medium-sized entrepreneurs (SMEs) in Lamongan, with Baitul Tamwil Muhammadiyah (BTM) Mulia Babat as the case study. The partial least square-structural equation modeling method is used in this quantitative study, examining data from 52 respondents, where the respondent data are BTM Mulia Babat business financing customers. The findings of this study found that Islamic microfinance services and business assistance directly have a positive impact on SMEs' increase in income. However, Islamic microfinance services and business assistance indirectly do not impact SMEs' welfare. Despite the increase in SMEs' income, it directly impacts SMEs' welfare. The novelty of this study is to identify the effectiveness of Islamic microfinance institutions in improving the welfare of SMEs. This study presents evidence of the impact of Islamic microfinance institutions on the welfare of micro and medium entrepreneurs. It can encourage more Islamic microfinance programs to offer feasible Islamic microfinance services as an alternative to boosting SMEs in the regions. This study's empirical implications and findings highlight the importance of business assistance from Islamic MIFs as business financing providers to support businesses.